Pola Perubahan, Wacana, dan Tren Konflik Sosial di Indonesia - Muliono, Muliono (Al-Adyan: Journal of Religious Studies, 2020)
The social history of Indonesia has recorded many types of conflict with serious impacts. The character of conflict in Indonesia has gradually changed. This study aims to elaborate the trends and patterns of the conflict changes in Indonesia, mapping the basic issues of the conflict, and offering the ideas of deconstruction to the discourse of plurality on ethnicity, religion, race, and inter-groups that tend to be seen as the causes of conflict. This study shows that the changing of violent conflict’s character in Indonesia is strongly influenced by the developments of a regime’s socio-economic and political climate dynamics. Under this reason, to understand the phenomenon of conflict in Indonesia cannot be strictly based on the plurality of ethnicity, religion, race, and inter-group issues, although the experiences of communal conflicts that have occurred have shown the ideological articulations that legitimize the use of violence related to ethnicity, class, and religious affiliation. Through the deconstructive approach, this study negates that the root of violent conflict comes from the character of local communality. On the contrary, the plurality of ethnicity, religion, and race should be seen as the social capital that worthwhile as the local mechanisms in resolving the various conflicts and as a means of empowerment.Sejarah sosial Indonesia mencatat banyak jenis konflik yang berdampak serius.  Karakter konflik di Indonesia berangsur-angsur berubah.  Penelitian ini bertujuan untuk mengelaborasi tren dan pola perubahan konflik di Indonesia, memetakan isu-isu dasar konflik, dan menawarkan gagasan dekonstruksi terhadap wacana pluralitas suku, agama, ras, dan antarkelompok yang cenderung dilihat sebagai penyebab konflik.  Studi ini menunjukkan bahwa perubahan karakter konflik kekerasan di Indonesia sangat dipengaruhi oleh perkembangan dinamika iklim sosial ekonomi dan politik suatu rezim.  Oleh karena itu, memahami fenomena konflik di Indonesia tidak dapat secara tegas didasarkan pada kemajemukan etnis, agama, ras, dan masalah antarkelompok, meskipun pengalaman konflik komunal yang terjadi telah menunjukkan artikulasi ideologis yang melegitimasi penggunaan kekerasan yang terkait dengan etnis, kelas, dan afiliasi agama.  Melalui pendekatan dekonstruktif, studi ini menyangkal bahwa akar konflik kekerasan bersumber dari karakter komunalitas lokal.  Sebaliknya, pluralitas suku, agama, dan ras harus dilihat sebagai modal sosial yang bermanfaat sebagai mekanisme lokal dalam menyelesaikan berbagai konflik dan sebagai sarana pemberdayaan.